169k views
16 votes
Factories:
x(x+1)-y(y+1)​

User Realtebo
by
5.6k points

2 Answers

13 votes

(x-y)(x+y+1)

Explanation:

x2+x-y2-y

(x+y)(x-y)+(x-y)

(x-y)(x+y+1)

User Davie
by
5.6k points
11 votes

Answer:


(x - y)(x + y + 1)

Explanation:


x(x + 1) - y(y + 1)

Lets expand it.


= > {x}^(2) + x - {y}^(2) - y

Lets re-arrange it.


= > {x}^(2) - {y}^(2) + x - y


= > (x + y)(x - y) + 1(x - y)

Lets take (x - y) common.


= > (x - y)[(x + y) + 1]


= > (x - y)(x + y + 1)

User JJSmith
by
5.8k points